1988
DOI: 10.1093/rheumatology/27.3.227
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indomethacin on the Psychomotor Function of Patients With Rheumatic Diseases

Abstract: We have compared the effect of single and multiple doses of indomethacin and placebo on objective measurements of psychomotor impairment in patients. Following a single 50 mg dose (n = 8), indomethacin produced psychomotor disturbance in only those patients who had no recent history of NSAID exposure. After multiple doses of indomethacin (25 and 50 mg tid for 5 days), significant psychomotor impairment was observed. We conclude that other NSAIDs may induce cross-tolerance to the psychomotor effects of indometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…These findings were in agreement with the fact that tolerance to NSAIDs in humans had been suspected for a long time [44,45,46,47], and some clinical conditions, like medication overuse headache, can perhaps be interpreted as a withdrawal syndrome [48]. Also, systemic administration of diflunisal, a salicylic derivative, causes pharmocodynamic tolerance in rats [49], and ibuprofen, a well known NSAID, seems to induce tolerance in humans [50].…”
Section: The Descending Pain Control System and Nsaid-induced Tolesupporting
confidence: 88%
“…These findings were in agreement with the fact that tolerance to NSAIDs in humans had been suspected for a long time [44,45,46,47], and some clinical conditions, like medication overuse headache, can perhaps be interpreted as a withdrawal syndrome [48]. Also, systemic administration of diflunisal, a salicylic derivative, causes pharmocodynamic tolerance in rats [49], and ibuprofen, a well known NSAID, seems to induce tolerance in humans [50].…”
Section: The Descending Pain Control System and Nsaid-induced Tolesupporting
confidence: 88%
“…Pullar et al . reported tachypylaxis after administration of lower doses (25 and 50 mg) of indomethacin in rheumatic patients during 5 days, while in our study after 2.5 days steady‐state was just reached.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition, the present study showed that tasks which are even more attention demanding remained unaffected by indomethacin despite the frequently reported CNS side effects such as dizziness, drowsiness and headaches. In theory, tachyphylaxis could have occurred and underlie the absence of psychomotor effects after administration of indomethacin . However, this seems unlikely for the present study since indomethacin was only administered for 2.5 days and, to the best of our knowledge, in the highest dose ever studied in similar research.…”
Section: Discussionmentioning
confidence: 78%
“…1985). It was then found that the psychomotor effects induced by test doses of indomethacin were less likely to occur in patients that were under treatment with indomethacin or similar analgesics, than in patients that were under no treatment (Pullar et al . 1988).…”
Section: Discussionmentioning
confidence: 99%